Hybrid governance: The integration of legacy and contemporary business administration in the Yogyakarta Royal Palace - Noviana Tursanurohmad; Made Wilantara (JURNAL ILMU SOSIAL, 2026)
This study critically analyzes how the Yogyakarta Palace integrates traditional administrative systems and modern business administration within its governance structure, evaluating its potential to balance cultural preservation with organizational efficiency. Employing a qualitative approach with an organizational ethnography design, the analysis involved participant observation, in-depth interviews, and document analysis. Results show that the Palace adopts a hybrid governance model and normatively acknowledges the need for modernization, with cultural leadership remaining central to decision-making. However, crucial operational tensions and a clash of institutional logics remain significantly prevalent. Identified challenges include the friction between traditional devotion and professional merit, the rigid formalization of royal decrees into standardized operating procedures, and the dilemma between cultural sacrality and measured commodification. The study concludes that while the integration of modern administrative tools offers a strong operational foundation, its efficacy in fostering genuinely adaptive cultural governance depends on a continuous process of Vernacular Modernization. Ultimately, this research produces the Javanese Cultural Hybrid Governance Framework to realize the transformative potential and sustainability of traditional monarchical institutions.